Manganese-Lead-Lead Dioxide Glass Ceramics as Electrode Materials. Issue 16 (2nd December 2019) - Rada, S.; Unguresan, M.; Rada, M.; Cuibus, D.; Zhang, J.; Pengfei, A.; Suciu, R.; Bot, A.; Culea, E.
Abstract : Glass ceramics in the xMnO2 ·(100-x)[4PbO2 ·Pb] system where x = 0-20% MnO2  were prepared and investigated by XRD, SEM, FTIR, UV-Vis, PL, EPR, Raman and XAFS spectroscopies and cyclic voltammetry measurements. The FTIR and Raman data indicate that the accommodation of the structure with the increasing of manganese content can be realized by the intercalation of [MnOn ] and [PbOn ] structural units and the formation of Mn-O-Mn linkages. The XANES and EXAFS data show that for lower dopant contents manganese ions adopt octahedron configurations distorted by oxygen while at higher dopant concentrations the structure of the host matrix is mainly composed of [MnO4 ] structural units and some [MnO6 ] structural units. EPR data show the presence of resonance lines characteristic of Mn +2 ions and depend on the manganese content of samples. Analysis of UV-Vis and PL data indicates the electronic transitions assigned to the Pb +2, Mn +2 and Mn +3 ions. An increase in the MnO2 concentration between 8 ≤ x ≤ 15 mol% indicates a good reversibility of the cyclic voltammogram and removes the passivation phenomenon of the anode electrode by an increase of the residual current intensity in the 0 to 2V potential range.